Comparison of prophylaxis effects against catheter -associated infection between antibiotic and heparin sealing-up way in central venous catheterization:a meta-analysis - ZHOU Xiang; YAO Yuan; ZHOU Xu-lin; JIANG Hong; XU Shi-ru (Linchuang shenzangbing zazhi)
Objective To evaluate systematically the clinical effect of antibiotic and heparinsealing-up ways was in central venous catheterization injection for prevention against catheter-associated infection in patients with hemodialysis. Methods Computer retrieval in MEDLINE, PubMed, The Cochrane Library, CBM, CNKI, Wanfang and other databases were performed. Randomized controlled trials(RCTs) of the effect of antibiotic and heparin sealing-up ways were collected. Two researchers screened the literature independently and used software Rev Man 5.3 for statistical analysis. Results There were 40 articles of RCTs in total, including 31 English ones and 9 Chinese ones. The results of meta-analysis showed that the infection rate of the antibiotic group was lower than that of the heparin group, with difference of statistical significance [OR=0.34,95%CI(0.30-0.38), I~2=39%,P<0.01]. Subgroup analysis showed that the rate of catheter exit infection in the antibiotic group was lower than that in the heparin group, with statistically significant difference [OR=0.83,95%CI(0.67-1.02),I~2=0%,P= 0.07]. The 365-day survival rate without catheter-associated infection in the antibiotic group was higher than that in the heparin group, with statistically significant difference[OR=-5.43,95%CI(3.53-8.35),I~2=0%,P<0.01]. The catheter-indwelling time in the antibiotic group was longer than that in the heparin group, with statistically significant difference [SMD=1.04,95%CI(0.27-1.82),I~2=100%,P<0.01]. The incidence of thrombus in the antibiotic group was lower than that in the heparin group, with statistically significant difference [OR=0.65,95%CI(0.46-0.90),I~2=32%,P<0.05]. The mortality rate of the antibiotic group was lower than that of the heparin group, with statistically significant difference [OR=0.53,95%CI(0.38-0.74),I~2=42%,P<0.01].Conclusions This results from this study show, for patients with hemodialysis through the vascular access of central venous catheterization, the use of antibiotic sealing-up way to prevent against catheter-associated infectionhas better effect than the pure Heparin sealing-up way, but the feasibility of antibiotics needs to be further discussed.